Caught in the middle: The role of the Facilities Manager in organisational energy use. (October 2015) - Goulden, Murray; Spence, Alexa
Abstract: This study analyses the role of the Facilities Manager [FM] as a key actor in organisational energy management. This builds on the idea that 'middle' agents in networks can be an important lever for socio-technical change. The study demonstrates the considerable impact the FM can have on workplace energy consumption, whilst identifying a number of factors that constrain their agency and capacity to act. These include demands to meet workforce expectations of comfort; a lack of support from senior management; and a shortage of resources. Underlying these challenges, the study identifies three different energy rationales – that is to say conceptual frameworks – which are deployed by different groups of organisational actors. The challenges of reconciling these at-times-contradictory rationales results in a picture of energy management which to the outsider can appear highly irrational. The paper concludes with a consideration of how policy makers can apply these insights to support energy reduction in workplaces. Highlights: Facilities Managers are increasingly critical node in organisational use of energy. Potential for FMs to make significant reductions to organisational energy use. Their ability to do so is constrained by the organisational environment. Three 'energy rationales' which the shape organisational context are identified. Opportunities exist for policy makers to improve organisational energy management.